2006
DOI: 10.1007/s00415-006-0318-5
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced Ultrasound in Dermatomyositis- and Polymyositis

Abstract: Increased skeletal muscle perfusion measured by CEUS could serve as an additional measurer for the diagnosis of an inflammatory myopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 24 publications
0
36
0
8
Order By: Relevance
“…Several complications such as intraventricular hemorrhage (IVH), acute hydrocephalus, early hematoma expansion, and perihemorrhagic edema may occur during hospital stay and have been previously verified to independently impact outcome [2][3][4][5][6]. In addition, recent studies reported a high rate of cardiac complications presumably linked to a further increase in mortality of patients with intracranial hemorrhage [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several complications such as intraventricular hemorrhage (IVH), acute hydrocephalus, early hematoma expansion, and perihemorrhagic edema may occur during hospital stay and have been previously verified to independently impact outcome [2][3][4][5][6]. In addition, recent studies reported a high rate of cardiac complications presumably linked to a further increase in mortality of patients with intracranial hemorrhage [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Power Doppler and contrast enhancement ultrasound have been found to show signs of increased perfusion in dermatomyositis and polymyositis. 2,3 This was also highlighted by Dr. Visser. Further prospective studies are needed to determine the diagnostic value of this technique, especially with regard to differentiating inflammatory myopathies from other neuromuscular disorders, or even to distinguish DM from PM based on the characteristics of power Doppler imaging combined with other ultrasound parameters.…”
Section: Replymentioning
confidence: 83%
“…However, although T2-weighted hyperintensities, i.e., edema-like changes [1], in muscles may be an early sign of a myositis, they may be misleading, because they also occur in other conditions including metabolic or traumatic changes, neuropathies, muscular dystrophies, myotonic dystrophy, necrotic changes such as rhabdomyolysis or diabetic muscle infarction or even physical exercise [24,25,46,47,51]. CEUS demonstrates in patients with typical histological features of PM and DM a significantly increased muscle perfusion in both subsets with comparable accuracy to MRI [29,52]. Since edemalike changes are detected in most patients with myositis, and in these are associated with increased perfusion detected by CEUS [29,52], both findings are suspicious for a myositis.…”
Section: Diagnosismentioning
confidence: 92%